Genome Editing With TALEN, CRISPR-Cas9 and CRISPR-Cas12a in Combination With AAV6 Homology Donor Restores T Cell Function for XLP - Houghton, Benjamin C.; Panchal, Neelam; Haas, Simone A.; Chmielewski, Kay O.; Hildenbeutel, Markus; Whittaker, Thomas; Mussolino, Claudio; Cathomen, Toni; Thrasher, Adrian J; Booth, Claire (Frontiers in Genome Editing, 2022)
X-linked lymphoproliferative disease is a rare inherited immune disorder, caused by mutations or deletions in the SH2D1A gene that encodes an intracellular adapter protein SAP (Slam-associated protein). SAP is essential for mediating several key immune processes and the immune system - T cells in particular - are dysregulated in its absence. Patients present with a spectrum of clinical manifestations, including haemophagocytic lymphohistiocytosis (HLH), dysgammaglobulinemia, lymphoma and autoimmunity. Treatment options are limited, and patients rarely survive to adulthood without an allogeneic haematopoietic stem cell transplant (HSCT). However, this procedure can have poor outcomes in the mismatched donor setting or in the presence of active HLH, leaving an unmet clinical need. Autologous haematopoeitic stem cell or T cell therapy may offer alternative treatment options, removing the need to find a suitable donor for HSCT and any risk of alloreactivity. SAP has a tightly controlled expression profile that a conventional lentiviral gene delivery platform may not be able to fully replicate. A gene editing approach could preserve more of the endogenous regulatory elements that govern SAP expression, potentially providing a more optimum therapy. Here, we assessed the ability of TALEN, CRISPR-Cas9 and CRISPR-Cas12a nucleases to drive targeted insertion of SAP cDNA at the first exon of the SH2D1A locus using an adeno-associated virus serotype 6 (AAV6)-based vector containing the donor template. All nuclease platforms were capable of high efficiency gene editing, which was optimised using a serum-free AAV6 transduction protocol. We show that T cells from XLP patients corrected by gene editing tools have restored physiological levels of SAP gene expression and restore SAP-dependent immune functions, indicating a new therapeutic opportunity for XLP patients.